Informing Education Research and the Praxis of Leadership through the use of Autoethnography and Phenomenology - Lisa J Starr (Canadian Society for Studies in Education, 2014)
For the purpose of this paper, I outline how phenomenology and autoethnography can be used to inform educational research and the praxis and educational leadership. I orient the reader by establishing the parameters for what is intended here in the use of the terms educational research and the praxis of educational leadership. Additionally, I offer explanations of both autoethnography and phenomenology, their value in educational research and specifically, their value in studying educational leadership.